The intelligent investor : a book of practical counsel - Graham, Benjamin, 1894-1976.; Zweig, Jason (New York : HarperBusiness Essentials, 2003)
Benjamin Graham taught the philosophy of "value investing" -- which shields investors from substantial error and teaches them to develop long-term strategies. Over the years, market developments have proven Graham's strategies. While preserving Graham's original text, this revised edition includes updated commentary by financial journalist Jason Zweig, whose perspective incorporates the realities of today's market, draws parallels between Graham's examples and today's financial headlines, and gives readers a more thorough understanding of how to apply Graham's principles.
Introduction: What this book expects to accomplish -- Investment versus speculation: Results to be expected by the intelligent investor -- The investor and inflation -- A century of stock-market history: The level of stock prices in early 1972 -- General portfolio policy: The defensive investor -- The defensive investor and common stocks -- Portfolio policy for the enterprising investor: Negative approach -- Portfolio policy for the enterprising investor: The positive side -- The investor and market fluctuations -- Investing in investment funds -- The investor and his advisers -- Security analysis for the lay investor: General approach -- Things to consider about per-share earnings -- A comparison of four listed companies -- Stock selection for the defensive investor -- Stock selection for the enterprising investor -- Convertible issues and warrants -- Four extremely instructive case histories -- A comparison of eight pairs of companies -- Shareholders and managements: Dividend policy -- "Margin of safety" as the central concept of investment -- Postscript -- Appendixes. The superinvestors of Graham-and-Doddsville -- Important rules concerning taxability of investment income and security transactions (in 1972) -- Basics of investment taxation (updated as of 2003) -- The new speculation in common stocks -- A case history: Aetna Maintenance Co. -- Tax accounting for NVF's acquisition of Sharon Steel shares -- Technological companies as investments.
"The definitive book on value investing"--Cover.
Includes bibliographical references (pages 579-587) and index.
Keywords: Securities; Investments